Optimal Distribution of Cargo Flows in the Multi-Network of Road and Rail Transport (Eurasian Journal of Engineering and Technology, 2022)
An urgent problem is the development of freight flows with the best use of transportation means of automobile and railway transport, the transport network, as well as their development, taking into account the prospective growth of freight flows. This will allow to deliver products to domestic and foreign markets and reduce their cost. This article presents a method for solving the problem of optimizing freight traffic in an expanded unified transport network and developing a transport network that includes road and rail transport.